English - Braghiroli, Stefano (Journal of Regional Security, 2023)
Russia’s attack of Ukraine lunched in February 2022 has turned the Kremlin into a political pariah. Traditionally Russia-friendly parties are increasingly faced with the dilemma of how to deal with new Russia’s image and how to frame the war in Ukraine. Since the Kremlin has been traditionally engaging in a multi-channel trans-ideological communication with both radical left and far-right, the two extremes of the political continuum appear equally affected. This piece will discuss and critically assess strategies and short-term tactics as well as attached narratives of such parties both at the national and European level. Specific attention will be devoted to the cases of Italy, France, and Germany.